The Implementation of Knowledge Management Based On Web 2.0 on Social News Site Hipwee - Cahyani, Mufida (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
The emergence of various kinds of social media applications does not only affect the way people communicate, but also penetrates into the realm of online mass media. Social media platforms that carry the concept of web 2.0 namely user generated content and network effects make it easy for a news to become viral in a short time, regardless of the validity and accuracy of the news. Web 2.0 itself is a direct application of the concept of Knowledge Management (KM) which emphasizes collaboration and user participation, but in a broader domain, it is slightly different from KM which emphasizes internal organizational participation. Hipwee as one of the social media-based online news sites applies both concepts to its content management. The purpose of this study was to analyze the extent of the application of KM in relation to Web 2.0. The method used to explore data through interviews with Hipwee managers and direct observation to the office location and also the Hipwee site. The results obtained are that the adaptation of the KM concept has not been applied to Web 2.0 on the Hipwee site, namely the concept of data mining, while the Web 2.0 concept has been applied to KM, namely unbounded collaboration, user generated content and network effects.